Kontribusi Perceived Parental Expectations terhadap Career Decision Mahasiswa Akhir Psikologi di Sumatera Barat - Rodatul Jannah; Zulmi Yusra (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study aims to determine the contribution of perceived parental expectations to the career decision of final psychology students in West Sumatra. The research method used is quantitative research with a correlational approach. This study involved 247 final students of psychology in West Sumatra, with an age range of 21-25 years. Data on perceived parental expectations was collected using the PPE (Perceived Parental Expectations) scale by Sasikala and Karunanidhi (2011), which was then translated by Marhaenayu (2020). Then career decision data was collected using the CDM (Career Decision Making) scale compiled by Dewi (2017). The research data was analyzed using a simple regression analysis technique. The results of the study showed that perceived parental expectations contributed 7.4% to the career decisions of final psychology students in West Sumatra. From the results of the study, it was concluded that there was a positive contribution between perceived parental expectations to the career decisions of final psychology students in West Sumatra.